2008
DOI: 10.1016/j.ajhg.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Two Sources of the Russian Patrilineal Heritage in Their Eurasian Context

Abstract: Progress in the mapping of population genetic substructure provides a core source of data for the reconstruction of the demographic history of our species and for the discovery of common signals relevant to disease research: These two aspects of enquiry overlap in their empirical data content and are especially informative at continental and subcontinental levels. In the present study of the variation of the Y chromosome pool of ethnic Russians, we show that the patrilineages within the pre-Ivan the Terrible h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
1
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 53 publications
8
93
1
13
Order By: Relevance
“…Notably, genetic boundaries were determined to a greater extent by geographic rather than linguistic boundaries, ie, genetic boundaries between Hungary and its neighbors were not significant relative to continental geographic boundaries (Rosser et al, 2000). In separate studies, Poles and Ukrainians were found to share a common patrilineal heritage together with southwestern Russians (Balanovsky et al, 2008) while Poles and Germans were genetically separated according to the present political boundary (Kayser et al, 2005). Nevertheless, intraEuropean selection signatures on AVPR1B have not been studied and thus any correlation with patrilineal boundaries is speculative.…”
Section: Consortium 2010mentioning
confidence: 99%
“…Notably, genetic boundaries were determined to a greater extent by geographic rather than linguistic boundaries, ie, genetic boundaries between Hungary and its neighbors were not significant relative to continental geographic boundaries (Rosser et al, 2000). In separate studies, Poles and Ukrainians were found to share a common patrilineal heritage together with southwestern Russians (Balanovsky et al, 2008) while Poles and Germans were genetically separated according to the present political boundary (Kayser et al, 2005). Nevertheless, intraEuropean selection signatures on AVPR1B have not been studied and thus any correlation with patrilineal boundaries is speculative.…”
Section: Consortium 2010mentioning
confidence: 99%
“…This is reflected in the haplogroup distribution: the Scandinavian haplogroup I occurs with frequencies 430% only in western Finland. 4 Haplogroup N3, typical for Fenno-Ugric populations of north-eastern Europe, 48,50 is observed in all parts of Finland but reaches high frequencies (B79%) only in eastern Finland. The interregional dichotomy results in large F ST estimates between eastern and western Finland and, consequently, in the clustering of populations (Figures 3 and 4).…”
Section: Gene Flow From Scandinaviamentioning
confidence: 99%
“…R1a was identified in excavated DNA in Germany with the dating of 4600 ybp (Haak et al, 2008), in Siberia, with the dating of 3800 -3400 ybp (Keyser et al, 2009), in Tarim Basin, Xinjiang, China, with the dating of ~4000 ybp (Li et al, 2010). Its distribution was described in various parts of Eurasia (e.g., Wells et al, 2001;Behar et al, 2003;Cinnioglu et al, 2004;Kharkov et al, 2004;Sengupta et al, 2006;Balanovsky et al, 2008;Sharma et al, 2009;Underhill et al, 2009;Abu-Amero et al, 2009). However, only in the last few years, thank mainly to efforts of Dr. Peter Underhill's laboratory at Stanford University, Dr. Thomas Krahn of Family Tree DNA's Genomics Research Center, and researchers of 1000 Genomes Project, many new SNPs in haplogroup R1a have been discovered; as indicated by beginning letters M, L, and Z, respectively, in the SNPs below.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of descendants of the ancient peoples who carry European R1a live in Eastern Europe, primarily in Russia (up to 63% of the population) and Poland, Ukraine, Belarus (up to 57% of the population in the last three countries) Balanovsky et al, 2008;Kayser et al, 2005;Kharkov et al, 2004Kharkov et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%